Trend and status of the Golden Eagle Aquila chrysaetos breeding population in the northern Apennines: Results from 20-years of monitoring (Avocetta, 2017)
The historical occurrence of the Golden Eagle Aquila chrysaetos in the Northern Apennines is supported by many documentary evidences, and confirmed by several toponyms that include the Italian term “aquila” referred to mountainous locations near nesting sites or where this raptor was frequently observed. This raptor was probably more widespread in the past and faced a strong demographic decline due to centuries of human persecution until 1977, when the killing of raptors was definitively banned in Italy. Nevertheless, a number of breeding pairs survived in the wildest locations of the Apennines, most of which were gradually included inside protected areas. Studies on the status of the Northern Apennines’s breeding population date back to the 1980s (Fasce & Fasce 1984) when a total of 8-10 breeding pairs was reported. Updated reports were published some years later by Chiavetta (1994), Chiavetta (2001) and Fasce & Fasce (2003). An improved collection of standardized data from the late 1990s, achieved through the coordination of volunteers from different regions of the study area (Liguria, Tuscany, Emilia-Romagna) resulted in two more recent reports (Magrini & Perna 2007, Schiassi et al., 2013). Currently the monitoring of the breeding population is supported by over 20 observers through regular controls of known pairs and home ranges, according to a standardized field protocol.